[ k = 1 ∑ 1 0 0 0 k ( ⌈ lo g 2 k ⌉ − ⌊ lo g 2 k ⌋ ) ] ( m o d 1 0 0 0 ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Log in to reply
Hahaha. Thanks for that. :)
Log in to reply
Log in to reply
@Parth Lohomi – Jim Rockford was the best! Thanks for this, and for the Einstein image; poor Albert looks like he lost his keys, or maybe just his Theory of Everything. :P
Lol this is an AIME question.
Same way! Easy question
Problem Loading...
Note Loading...
Set Loading...
We will have ⌈ lo g 2 k ⌉ − ⌊ lo g 2 k ⌋ = 1 for all positive integers k except for the non-negative integer powers of 2 , for which the difference is 0 .
Thus N = k = 1 ∑ 1 0 0 0 k − n = 0 ∑ 9 2 n = 5 0 0 ∗ 1 0 0 1 − 1 0 2 3 ≡ 4 7 7 ( m o d 1 0 0 0 ) .